Personne privée, personnage public - Marc Lits (Communication)
The news is not a raw account of an event, but a narrativisation which foregrounds media personalities. The latter might favour the investment of the reader, but their stereotypical construction may also remove complex facts from their context. This treatment becomes more delicate in a postmodern society where the distinction between the public and private spheres is blurred. Without being excessively moralising, it is imperative to measure the de-ontological and ethical consequences of this personalization of news in both the printed press and in the way that the media is consumed.